Evaluation of the New Micronaut-Candida System Compared to the API ID32C Method for Yeast Identification - Szabó, Z. (American Society for Microbiology (ASM), 2008)
A new system, Micronaut-Candida, was compared to API ID32C to identify 264 yeast (Candida albicans, C. parapsilosis, C. tropicalis, C. krusei, C. inconspicua, C. norvegensis, C. lusitaniae, C. guilliermondii, C. dubliniensis, C. pulcherrima, C. famata, C. rugosa, C. glabrata, C. kefyr, C. lipolytica, C. catenulata, C. neoformans, Geotrichum and Trichosporon species, Rhodotorula glutinis, and Saccharomyces cerevisiae) clinical isolates. Results were in concordance in 244 cases. Eighteen out of the 20 of discordant results were correctly identified by Micronaut-Candida but not by API ID32C, as confirmed by PCR ribotyping.